Detection of sand encroachment patterns in desert oases: the case of Erg Chebbi (Morocco) - Puy, Arnald; Herzog, Manuel; Bubenzer, Olaf (The science of the total environment, 2018)
Desert oases are fragile agrarian areas, very vulnerable to sand encroachment by wind. Ensuring their conservation highly depends on our capacity to identify sand encroachment patterns, e.g. the origin of sand and its spatial distribution in the irrigated plots. Here we show how to tackle this issue using the case study of Erg Chebbi (Morocco), where two oases (Hassilabiad and Merzouga) are surrounded by dunes, Hamada and alluvial sediments from the Wadi Ziz. We combine field interviews with the study of wind dynamics, sediment sampling, Particle Size Distribution (PSD) tests and End-Member Modelling Analysis (EMMA). We observe that the most relevant contributor to sand encroachment is the Wadi Ziz (30%), followed by the Hamada (28%), an undetermined source of dust (25%), and the Erg dunes (16%). These genetically different sediments cluster unevenly in the oases, indicating the existence of areas with contrasting degrees of exposure to sedimentary sources. The results allow to define on solid grounds which sand source areas should be stabilized first in order to obtain the greatest reduction in sand encroachment. Our approach also provides policy-makers with better tools to identify which spots are specially vulnerable to accumulate a specific sediment, thus allowing for a more nuanced management of sand in oasis environments.
Gesehen am 18.05.2020